Exploring Gender-Based Preferences in TikTok Influencer Following Among Students at University of Technology - Khulula Blessing Mthembu; Xolisa Philip Poyise; Phomolo Motsilili; Murimo Bethel Mutanga; Zvinodashe Revesai (Indonesian Journal of Information Systems, 2026)
The rise of short-form video platforms has fundamentally changed patterns of digital communication, with TikTok becoming a dominant influence in youth media consumption. However, gender-specific preferences in influencer choice remain underexamined, especially within African university settings. Based on Uses and Gratifications Theory (UGT), this qualitative exploratory study investigates how gender affects TikTok influencer following behaviours among 103 South African university students who were active TikTok users. Data were gathered via open-ended online questionnaires and analysed through Qualitative Content Analysis with dual-researcher coding to ensure reliability. Significant gender-based differences appeared in influencer preferences and motivational factors: male students (61% of the sample) mainly followed educational, motivational, and entrepreneurial influencers, seeking cognitive gratifications related to skill development and career prospects, while female students (39% of the sample) inclined towards lifestyle, beauty, and fashion influencers, prioritising affective gratifications like emotional resonance, identity exploration, and self-expression. Despite these differences, both groups valued influencer authenticity, relatability, and expertise over follower count or popularity metrics. The findings extend UGT application to algorithm-driven, short-form video platforms and show how gender influences digital media gratification-seeking behaviours, revealing TikTok as a multifaceted tool for identity building, emotional validation, and aspirational learning rather than just entertainment. These results inform gender-sensitive digital marketing, educational technology integration, and culturally relevant content creation for African youth markets, allowing universities to use these insights for more effective student engagement on social media. The study's focus on a single institution and its cross-sectional design limit broad applicability, indicating that future research should explore long-term influencer relationships and cross-cultural comparisons across African educational contexts. Keywords: Gender differences, social media, influencer preferences, TikTok, university students, Uses and Gratifications Theory